The fetal safety of clomiphene citrate: a population‐based retrospective cohort study. (15th May 2017) - Weller, A; Daniel, S; Koren, G; Lunenfeld, E; Levy, A
Abstract : Objective: To evaluate whether exposure to clomiphene citrate (CC) for ovulation induction is associated with major malformations overall or with specific fetal anomalies. Design: We conducted a population‐based retrospective cohort study. Exposure was defined as CC dispension from 2 months before conception through the first month of pregnancy. Settings: Four databases were combined: medication, birth, hospitalization, and terminations of pregnancy. Population: The study included all women in southern Israel who gave birth or underwent termination of pregnancy at Soroka Medical Center, from 1998 to 2009. Methods: The rates of major malformations overall and six different subcategories of anomalies were evaluated. The crude odds ratio (OR) was calculated with a 95% confidence interval (95% CI). Subsequently the adjusted odds ratio (aOR) was calculated using multiple logistic regression models controlling for maternal age, pre‐pregnancy diabetes, parity, ethnicity, the calendar year in which the birth/termination of pregnancy took place, smoking, and the use of gonadotropins and progesterone. Main outcome measures: Major malformations overall and specific fetal malformations by organ systems. Results: Of 114 961 pregnant women, 1872 were exposed to CC. No association was detected between exposure to CC and rates of major malformations overall (aOR 1.08, 95% CI 0.88–1.32) or rates of subcategories of malformations. Exposure was not associated with anencephaly (aOR 2.27, 95% CI 0.44–11.71) or oesophageal atresia (aOR 3.681, 95% CI, 0.65–20.76). Conclusions: In this large population‐based retrospective cohort study, exposure to CC was not associated with an increased risk of either rates of major malformations overall or rates of specific malformations. Tweetable abstract: An observational study: no increased risk for fetal malformations following exposure to clomiphene citrate. Tweetable abstract: An observational study: no increased risk for fetal malformations following exposure to clomiphene citrate.